Babalu Art Reconstruction in Batang:Roland Barthes' Semiotic Analysis - Galuh Fatma Hedianti; Agus Cahyono; Sunarto Sunarto (International Conference on Science, Education, and Technology, 2022)
The purpose of this research is to analyze and interpret the timeline of Babalu art and analyze to find the production and consumption of the meanings contained in the signs of the various movements of the Babalu Dance in the contemporary era. This research uses a qualitative approach with semiotic methods. Data and data sources come from primary data (artists, culturalists, and the people of Pekalongan-Batang) and secondary data comes from documents or historical records and events in Pekalongan-Batang and related scientific articles about the Babalu art. Data collection techniques were carried out by in-depth interviews, participant observation, document studies, and life history analysis. Data analysis was carried out by digging deeper into how the meaning of various movements is conveyed through signs in an archive, historical records, and historical events. The results showed that Babalu art is a folk art from the north coast of Java. Babalu art performances combine drama (implied messages about meaning in life), literature (moral speech), music (flying, kentongan, accordion), dance (insert fragments between acts). Pure motion is used in the Babalu Dance as a connecting and sweetening movement in the Babalu Dance performance, and the various meaningful movements of the Babalu Dance are analyzed using denotative and connotative meanings which result in the conclusion that the various meaningful movements in the Babalu Dance represent the meaning of human life, both physical and metaphysical.